2017 ACC/AHA/HFSA Focused Update of the 2013 ACCF/AHA Guideline for the Management of Heart Failure: A Report of the American College of Cardiology/American Heart Association Task Force on Clinical Practice Guidelines and the Heart Failure Society of America. Issue 6 (8th August 2017) - Yancy, Clyde W.; Jessup, Mariell; Bozkurt, Biykem; Butler, Javed; Casey, Donald E.; Colvin, Monica M.; Drazner, Mark H.; Filippatos, Gerasimos S.; Fonarow, Gregg C.; Givertz, Michael M.; Hollenberg, Steven M.; Lindenfeld, JoAnn; et al.
Abstract : Supplemental Digital Content is available in the text.